Panel sequencing links rare, likely damaging gene variants with distinct clinical phenotypes and outcomes in juvenile-onset SLE. (9th May 2022) - Charras, Amandine; Haldenby, Sam; Smith, Eve M D; Egbivwie, Naomi; Olohan, Lisa; Kenny, John G; Schwarz, Klaus; Roberts, Carla; Al-Abadi, Eslam; Armon, Kate; Bailey, Kathryn; Ciurtin, Coziana; et al.
Abstract: Objectives: Juvenile-onset systemic lupus erythematosus (jSLE) affects 15–20% of lupus patients. Clinical heterogeneity between racial groups, age groups and individual patients suggests variable pathophysiology. This study aimed to identify highly penetrant damaging mutations in genes associated with SLE/SLE-like disease in a large national cohort (UK JSLE Cohort Study) and compare demographic, clinical and laboratory features in patient sub-cohorts with 'genetic' SLE vs remaining SLE patients. Methods: Based on a sequencing panel designed in 2018, target enrichment and next-generation sequencing were performed in 348 patients to identify damaging gene variants. Findings were integrated with demographic, clinical and treatment related datasets. Results: Damaging gene variants were identified in ∼3.5% of jSLE patients. When compared with the remaining cohort, 'genetic' SLE affected younger children and more Black African/Caribbean patients. 'Genetic' SLE patients exhibited less organ involvement and damage, and neuropsychiatric involvement developed over time. Less aggressive first line treatment was chosen in 'genetic' SLE patients, but more second and third line agents were used. 'Genetic' SLE associated with anti-dsDNA antibody positivity at diagnosis and reduced ANA, anti-LA and anti-Sm antibody positivity at last visit. Conclusion: Approximately 3.5% of jSLE patients present damaging gene variants associated with younger age at onset, and distinct clinical features. As less commonly observed after treatment induction, in 'genetic' SLE, autoantibody positivity may be the result of tissue damage and explain reduced immune complex-mediated renal and haematological involvement. Routine sequencing could allow for patient stratification, risk assessment and target-directed treatment, thereby increasing efficacy and reducing toxicity.